Integrated analysis of sexual maturation through successive growth instars in the spider crab Leurocyclus tuberculosus (Decapoda: Majoidea) - Gonzalez Pisani, Ximena (2017)
An integrative analysis of sexual maturity associated with growth was developed for the spider crab Leurocyclus tuberculosus (H. Milne Edwards and Lucas, 1842). Sexual maturity was characterized based on gonadal, morphological, morphometric, and functional sexual maturity. Progress in sexual maturation was described through 13 growth stages (instars) detected by the examination of size (carapace width) frequency distributions. Mature females displayed mature ovaries, developed vaginae, open gonopores, allometric changes in the abdomen, and ovigerous stage in the transition from instar IX to instar X. Sexually mature males presented spermatophores in the distal vasa deferentia and allometric changes in several measurements of the right chela in the transition from instar X to instar XI. However, two prepubertal phases were recognized in both sexes separated from each other by a prepubertal critical molt. Preceding the second critical molt, gonopores were sealed and vasa deferentia showed no spermatophores, and therefore neither sex was able to mate. The integrated analysis of size at maturity and size frequency distributions showed that in both sexes molt to gonadal, morphological, morphometric, and functional sexual maturity occurred in advance of the terminal molt, in contrast with patterns observed in other Majoidea.